SPECIFICS OF FINANCING PUBLIC PROCUREMENT IN THE REPUBLIC OF MOLDOVA IN THE CONTEXT OF OPTIMIZING PUBLIC FINANCE MANAGEMENT - MULIC, Andrei; ULIAN, Galina (Economy and Sociology, 2021)
Public procurement is investigated in terms of results and maximum efficiency of allocation of financial resources of the national public budget. In the context of economic development, optimization of the management of public financial resources is based on improving the legislation on public procurement and the financing mechanism. Based on this, public procurement is a complex, multi-level, interdependent system, the functioning at the all public levels. The aim of the research is to conduct a comprehensive study of the main problems and features of public procurement financing in order to optimize public finance management at the national level and to develop recommendations for improving the public procurement system in the Republic of Moldova. The methodology is based on the structural research method. The article is based on a study of the public procurement system in the Republic of Moldova, analyzing its constituent elements. The analytical method was used to study the concept of public procurement. The study established the relationship between the ethical behavior of officials, the effectiveness of control and the implementation of information systems to optimize the system of financing public procurement in the Republic of Moldova. Proposals are presented to improve the efficiency of the public financing mechanism in the context of electronic public procurement procedures within the automated information system “State Register of Public Procurements” MTender